Spatially confined electrochemical activity at a non-patterned semiconductor electrode - Choudhury, M.; Ciampi, Simone; Lu, X.; Kashi, M.; Zhao, C.; Gooding, J. (Pergamon, 2017)
© 2017 Elsevier LtdHerein we show that faradaic electrochemistry can be confined to a discrete region of a monolithic semiconducting electrode by means of locally addressing the kinetics of electron transfer with a focused light-pointer. A Si(100) electrode is modified with a self-assembled monolayer to which ferrocene is attached. The extent to which a model heterogeneous electrochemical reaction can be addressed in two-dimensions was explored at Si(100) photoanodes using scanning electrochemical microscopy operating in surface-generation/tip-collection mode. The link between the experimental radial profile of the catalytic current around the site of illumination and the substrate thickness indicates an inverse relationship between thickness and spatial resolution. We show to which extent the diffusion of charge carriers in the substrate governs the light-addressability. A spatial resolutions for our electrocatalytic system can be as low as ca. 385 µm (ca. 5-times the size of the light pointer) using a non-structured Si(100) photoanode configured as a single-wire device.